Managerial decisions in syndicated lending - A. A. Tarasov (Управление)
The syndicated lending market is one of the main financing sources for the development of the Russian economy. This article is dedicated to the processes managerial decision-making within the framework of syndicated lending transactions by borrowers, lenders and investors. Thanks to the use of market tools, borrowers get the opportunity to form an optimal structure for solving various tasks of corporate finance. Taking into account the adoption of managerial decisions by borrowers, the analysis of the following options for such decisions is presented: the choice of a bank for the role of a credit manager and the appointment of a legal adviser to the borrower. Lenders of syndicated lending transactions, making decisions on participation in transactions in the primary syndicated lending market, use the opportunity to share the specialized risks of syndicated transactions within the syndicate. Decisions that are made by the lenders include determining the commercial terms of participation in a syndicated loan in the primary market and approving these terms in accordance with the bank’s business processes. Investors active in the secondary syndicated lending market form their portfolios by making decisions regarding the following financial parameters of their transactions: the amount of the acquired/assigned interest in the syndicated lending participation and the transaction price. The paper concludes The article concludes that it is important for syndicated lending market participants to make optimal decisions, taking into account the role of market instruments in financing development projects of Russian corporations.